Stimulant Use in Patients with Sturge-Weber Syndrome: Safety and Efficacy - Lance, Eboni I. (Pediatr Neurol, 2013)
BACKGROUND: Sturge Weber Syndrome (SWS) is characterized by a facial port-wine birthmark, vascular eye abnormalities, and a leptomeningeal angioma. Attention and behavioral issues are common in SWS; however, literature evidence for stimulant treatment is minimal. This study evaluates stimulant medication safety and efficacy in SWS patients. METHODS: The research database of the Hunter Nelson Sturge-Weber Center (n = 210 subjects with SWS brain involvement) was reviewed for stimulant use. Twelve subjects (mean age 10.5 years, age range 4 to 21 years) on stimulants were seen between 2003 and 2012. A retrospective chart review obtained co-morbid diagnoses, stimulant type and dosage, medication side effects, vital signs, and medication efficacy. RESULTS: All twelve subjects had brain involvement (unilateral - nine; bilateral – three). Additional co-morbidities included epilepsy (twelve), hemi-paresis (eight), headaches (eight), and vision deficits (seven). Eight subjects reported side effects, primarily appetite suppression (four) and headaches (three). There were no statistically significant changes in weight or blood pressure six months after medication initiation. Medication efficacy was subjectively reported in eleven subjects. Seven patients remained on stimulants at their most recent follow up visit. CONCLUSIONS: This study preliminarily evaluates stimulant medication use in a small group of SWS patients. Stimulants were tolerated and effective in most subjects. Side effects were mostly minor and medication did not negatively impact growth or vital signs. Stimulant medication may be a safe and effective intervention for SWS children with attention issues/attention deficit hyperactivity disorder (ADHD). Further studies with larger sample sizes are needed.